2010
DOI: 10.1111/j.1442-2042.2010.02605.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of genital burns: A review

Abstract: Abstract:We review the etiology and the management strategy of genital burns. The incidence of genital burns ranges from 2.8 to 13%. Most are part of larger injuries. Scald burns are typical for children, whereas flame and chemical burns happen more often in adults. For first and second-degree genital burns, a conservative approach with physiological dressings and topical antimicrobials is advised. Only third degree burns need to be treated with removal of necrotic tissue and grafting. Indwelling catheters or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Michielsen and Lafaire have reported that genital burns accounted for 2.8-13% of burn-specific hospital admissions. 6 Scald burns are the most common cause of genital burns in children, whereas flame and chemical burns occur more frequently in adults. 6 A number of studies have reported on the morbidity of burns to the perineum, as well as the optimal treatment method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Michielsen and Lafaire have reported that genital burns accounted for 2.8-13% of burn-specific hospital admissions. 6 Scald burns are the most common cause of genital burns in children, whereas flame and chemical burns occur more frequently in adults. 6 A number of studies have reported on the morbidity of burns to the perineum, as well as the optimal treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…6 Scald burns are the most common cause of genital burns in children, whereas flame and chemical burns occur more frequently in adults. 6 A number of studies have reported on the morbidity of burns to the perineum, as well as the optimal treatment method. 2,[7][8][9] The vasculature of the perineum, the surrounding skin and genitourinary function might be compromised after a genital burn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the fact that scalds and thermal burns were of greater severity whereas the chemical burns tended to be more superficial. Abel et al reported that scalds and thermal burns were associated with larger TBSA burns than chemical burns, had a higher percentage of serial debridement (scalds 24.4%, thermal 33.7% and chemical 11.1%) and of greater than 10-day length of hospital stay (scalds 56.5%, thermal 26.3%, chemical 2.2%) [7].…”
Section: Yearmentioning
confidence: 99%
“…Single-institution studies have estimated the prevalence of genital burns (GB) between 1.7%-13% of burn hospital admissions [5][6][7]. Individuals with GBs are more likely to have higher total body surface area (TBSA) involvement; genitalia alone comprise 1% of TBSA and studies have demonstrated an average TBSA of 21%-56% for all patients with perineal burns [5].…”
Section: Introductionmentioning
confidence: 99%